The relationship between spiritual health and happiness in medical students during the COVID-19 outbreak: A survey in southeastern Iran - Abdolkarimi, Mahdi; Masoomi, Mahdieh; Lotfipur, Seyedeh Shirin; Zakeri, Mohammad Ali (Frontiers in Psychology, 2022)
It is necessary to study the various dimensions of health and their affecting factors during the coronavirus disease-19 (COVID-19) pandemic to identify the necessary interventions. The study aims to determine the relationship between spiritual health and happiness in medical students during the COVID-19 outbreak. In this analytical cross-sectional design study, 409 medical students were examined for the state of happiness and spiritual health and the relationship between them. Student information was collected through Web-based sampling by using standard tools from 20 April to 20 June 2020. Medical students completed the demographic questionnaire as well as Oxford Happiness Questionnaire (OHQ) and Paloutzian and Ellison spiritual health questionnaire. The results showed that while the score of spiritual health and happiness was related to factors such as marriage, interest in a field of study, and socioeconomic status, the relationship between spiritual health and happiness was significant (r = 0.72). This study showed that students’ happiness scores were not optimal during the COVID-19 pandemic. Due to the strong relationship between spiritual health and happiness scores, spiritual health promotion, in conjunction with other interventions, can be used to improve happiness in this group.